Beyond the big five as predictors of dispositions toward ridicule and being laughed at: The HEXACO model and the dark triad. Issue 5 (23rd June 2019) - Torres‐Marín, Jorge; Proyer, René T.; López‐Benítez, Raúl; Brauer, Kay; Carretero‐Dios, Hugo
Abstract : We aimed to extend research on dispositions toward ridicule and being laughed at by testing the localization of the fear of (gelotophobia) and the joy in (gelotophilia) being laughed at, and the joy in laughing at others (katagelasticism) in the HEXACO model and the Dark Triad traits (both have not been examined so far). Study 1 (HEXACO model: N = 216) showed that gelotophobia was related to low extraversion, high emotionality, and low honesty‐humility; gelotophilia to high extraversion and high openness to experience; and katagelasticism to low agreeableness and low honesty‐humility. These results were similar to prior findings based on the Five‐Factor model, and supported the notion that the honesty‐humility trait contributes to the prediction of individual differences in gelotophobia and katagelasticism. Study 2 (Dark Triad: N = 204) showed that gelotophobia was related to high Machiavellianism and low narcissism; gelotophilia to high narcissism; and katagelasticism to high psychopathy and high Machiavellianism. These data helped to clarify our findings on the honesty‐humility trait, showing that gelotophobes and katagelasticists differ in their socially aversive characteristics. Overall, this research provides empirical evidence that dark (but subclinical) traits can be seen as relevant personality predictors of how people deal with laughter and ridicule.